An optical fire detector with enhanced response sensitivities for black smoke based on the polarized light scattering. (5th September 2019) - Deng, Tian; Zeng, Jin; Wang, Shu; Yan, Shu; Chen, Ang
Abstract: Optical fire smoke detectors trigger the fire alarms when the scattering light intensity exceeds a preset threshold. Current optical detectors usually takes a long time or even fail to trigger a fire alarm for black smoke due to the strong absorption and weak scattering efficiency. A fire smoke sensor with dual polarized channels is proposed to adjust the response sensitivities to both white and black smoke. The white and black smoke can be discriminated by the polarization degree, and thus the response sensitivity can be adjusted by a correction factor. A prototype sensor is set up and tested by monodisperse aerosols with a maximum error of 10.1%. According to the experimental results, the prototype sensor could correctly differentiate white smoke and black smoke based on polarization degree, and the fire alarm for black smoke can be triggered as fast as for white smoke.